2006
DOI: 10.1186/1471-2164-7-184
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bacteria-challenged wild silkmoth, Antheraea mylitta (lepidoptera) transcriptome reveals potential immune genes

Abstract: Background: In the recent years a strong resemblance has been observed between the insect immune system and the mammalian innate immune mechanisms suggesting their common origin. Among the insects, only the dipterans (Drosophila and various mosquito species) have been widely investigated for their immune responses towards diverse pathogens. In the present study we constructed and analysed the immune transcriptome of the lepidopteran Antheraea mylitta, an economically important Indian tasar silkmoth with a view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 43 publications
(45 reference statements)
2
23
0
Order By: Relevance
“…They include 3 lysozymes, 1 attacin, and 1 potential AMP with the high identity (67%) to M. sexta immune-induced protein-1 (IID-1)26. So far, little is known about IID except it was reported that it was highly immune induced 26 and putatively defensive against the pathogens 39. Based on the amino acid sequence similarities, these five transcripts were named as OfgLys5, Ofglys6, OfgLys10, OfgAtt, and OfgIID.…”
Section: Resultsmentioning
confidence: 99%
“…They include 3 lysozymes, 1 attacin, and 1 potential AMP with the high identity (67%) to M. sexta immune-induced protein-1 (IID-1)26. So far, little is known about IID except it was reported that it was highly immune induced 26 and putatively defensive against the pathogens 39. Based on the amino acid sequence similarities, these five transcripts were named as OfgLys5, Ofglys6, OfgLys10, OfgAtt, and OfgIID.…”
Section: Resultsmentioning
confidence: 99%
“…So far, gloverins have been identified only in Lepidoptera , including H. armigera (Mackintosh et al, 1998a), T. ni (Lundstrom et al, 2002), G. mellonella (Seitz et al, 2003), Antheraea mylitta (Gandhe et al, 2006), M. sexta (Abdel-latief and Hilker, 2008; Xu et al, 2012), Diatraea saccharialis (Silva et al, 2010), Plutella xylostella (Etebari et al, 2011; Eum et al, 2007), S. exigua (Hwang and Kim, 2011), and B. mori (Kawaoka et al, 2008; Mrinal and Nagaraju, 2008). Gloverins are synthesized as pre-pro-proteins, and the N-terminal regions of pro-gloverins contain a conserved RXXR motif (Xu et al, 2012).…”
Section: Gloverinsmentioning
confidence: 99%
“…Seroins were initially discovered in Galleria mellonella as part of silk producing machinery (Zurovec et al ., ). Seroins have not been assigned any specific function in silk production in spite of their occurrence in the silkgland, whereas their induced expression was noticed in the fat body of G. mellonella and in Antheraea mylitta upon injury and bacterial challenge respectively (Gandhe et al ., ; Korayem et al ., ). Seroins are secretory proteins which possess signal peptides different from structural components of silk (Nirmala et al ., ).…”
Section: Introductionmentioning
confidence: 98%